Teachers’ Strategies in Developing Kitabah (Writing) Skills Among Madrasah Aliyah Students: A Descriptive Qualitative Study - Ade Arip Ardiansyah; Nahdhiyyatussholiha Nahdhiyyatussholiha; Ummul Mutmainnah (UIN Sunan Gunung Djati Bandung, 2026)
This study aims to describe the strategies used by teachers in developing students’ kitabah (Arabic writing) skills at Madrasah Aliyah. The research employs a descriptive qualitative approach, with the subjects consisting of Arabic language teachers and students from grades X to XII. Data were collected through observations, in-depth interviews, and documentation, and were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that teachers implement various strategies, including the use of the communicative approach, gradual practice (tadarruj), text modeling, and the provision of continuous feedback. In addition, teachers utilize learning media such as worksheets, authentic texts, and digital platforms to enhance students’ motivation and writing proficiency. Supporting factors for these strategies include teachers’ professional competence and the availability of learning resources, while inhibiting factors involve limited instructional time and the heterogeneity of students’ abilities. The study concludes that varied and contextually grounded teacher strategies play a significant role in the development of kitabah skills among Madrasah Aliyah students.